Pengaruh Keselamatan & Kesehatan Kerja (K3) dan Disiplin Kerja terhadap Produktivitas Karyawan Bagian Produksi pada PT. Sawit Asahan Indah Kecamatan Rambah Samo Kabupaten Rokan Hulu - Marlis '; Dewita Suryati Ningsih; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Sawit Asahan Indah Kecamatan Rambah Samo Kabupaten Rokan Hulu in order to determine how salvation and Health Effects of Work and Work Discipline either directly or indirectly Employee Productivity part of the production Kecamatan Rambah Samo Kabupaten Rokan Hulu. The sample in this study are 85 employees at PT. Sawit Asahan Indah, with testing data analysis used in this study is a Test Validity, reliability test, Test Classical Assumptions, Methods Msi. Data analysis method used is the method of path analysis or path analysis with the help of statistical package of social science version 20. From the results of the testing that has been done, it is evident that in partial safety & health and discipline of work have a significant influence on the productivity, safety and occupational health and discipline work together to have a significant influence on productivity and workplace safety and health impacts on productivity through labor discipline.So from this study the variables that should be improved productivity go round skills and the ability to use the tools of production employees are effective, the safety and health variables that should be improved is the direction and knowledge of the use of the machines, while the variables that should work discipline in is the increase in the company's adherence to the rules and complete the work on timeKeywords : Productivity, Health and Safety and Work Discipline.